Technical validation of the field guide for Participatory Rangeland Management (PRM), 27-28 October 2023 - Intergovernmental Authority on Development (2023)
IGAD and ILRI partnered and drafted a field guide for participatory rangelands management (PRM). ICPALD held a regional workshop to validate the draft participatory rangeland management (PRM) field guide from 27-28 October 2023 as a way of ensuring effective consultation, review and participation in strengthening the field guide that will support the cascading of a similar approach and practices in the IGAD member States.